Fabrication and electrical characterization of Al/p-ZnIn2Se4 thin film Schottky diode structure. (1st November 2016) - Dhruv, D.K.; Patel, B.H.
Abstract: Polycrystalline thin films of ternary ZnIn2 Se4 compound with p-type conductivity were deposited on a pre-deposited aluminium ( Al ) film by a flash evaporation technique. A Schottky diode comprising of Al/p-ZnIn2 Se4 structure was fabricated and characterized in the temperature range 303–323 K in dark condition. The Schottky diode was subjected to current ( I )-voltage ( V ) and capacitance ( C )-voltage ( V ) characterization. The Al/p-ZnIn2 Se4 Schottky diode showed behaviour typical of a p-n junction diode. The devices showed very good diode behaviour with the rectification ratio of about 10 5 at 1.0 V in dark. The Schottky diode ideality factor, barrier height, carrier concentration, etc. were derived from I-V and C-V measurements. At lower applied voltages ( V ≤0.5 V), the electrical conduction was found to take place by thermionic emission ( TE ) whereas at higher voltages ( V >0.5 V), a space charge limited conduction mechanism ( SCLC ) was observed. An energy band diagram was constructed for fabricated Al/p-ZnIn2 Se4 Schottky diode.